Does Talking Stick Improve Students’ Activities and Economic Learning Result? - Anggraini, Ines Widya; Hardinto, Prih (Classroom Action Research Journal (CARJO), 2019)
This study examines the relationship between talking stick and its impact on students’ activities and learning result. In addition the paper addressed to cope the existing problem in the classroom by implementing talking stick. The study followed a classroom action research using qualitative method. This study was conducted in two cycles consisting of three meetings for each. The findings showed that both the students’ activities and learning result in economics experienced an upward improvement during cycles. In more detail, in the first cycle, students’ activities were about 65.36 percent and rose to the level 83.1 percent. The results on the completeness of students’ learning outcomes was about 52.94 percent in the first cycle and increased to approximately 92.16 percent in the next cycle.Keywords: Talking Stick, Students’ Activities, Learning Outcomes